Thrombalexins: Cell‐Localized Inhibition of Thrombin and Its Effects in a Model of High‐Risk Renal Transplantation. Issue 1 (8th August 2016) - Karegli, J.; Melchionna, T.; Farrar, C. A.; Greenlaw, R.; Smolarek, D.; Horsfield, C.; Charif, R.; McVey, J. H.; Dorling, A.; Sacks, S. H.; Smith, R. A. G.
Abstract : Allograft transplantation into sensitized recipients with antidonor antibodies results in accelerated antibody‐mediated rejection (AMR), complement activation, and graft thrombosis. We have developed a membrane‐localizing technology of wide applicability that enables therapeutic agents, including anticoagulants, to bind to cell surfaces and protect the donor endothelium. We describe here how this technology has been applied to thrombin inhibitors to generate a novel class of drugs termed thrombalexins (TLNs). Using a rat model of hyperacute rejection, we investigated the potential of one such inhibitor (thrombalexin‐1 [TLN‐1]) to prevent acute antibody‐mediated thrombosis in the donor organ. TLN‐1 alone was able to reduce intragraft thrombosis and significantly delay rejection. The results confirm a pivotal role for thrombin in AMR in vivo . This approach targets donor organs rather than the recipient and is intended to be directly translatable to clinical use. Abstract : A new type of anticoagulant, created by linking a membrane‐binding element to a peptidic thrombin inhibitor, enables antithrombotic activity to be localized on cell surfaces, ameliorating microthrombosis and enhancing renal allograft survival in a hyperimmune recipient without inducing systemic anticoagulation.